Ethosomal gel for rectal transmucosal delivery of domperidone: design of experiment, in vitro, and in vivo evaluation - Wedad Sakran; Rania S. Abdel-Rashid; Fatma Saleh; Raghda Abdel-Monem (Taylor & Francis Group, 2022)
Despite high efficiency of domperidone (DOM) in prophylaxis of emesis accompanied with radiotherapy and chemotherapy, it still can bother cancer patients by its powerful side effects and difficulty of its oral administration. The study was designed to develop and optimize DOM loaded ethosomal gel for rectal transmucosal delivery. Ethosomal formulations were prepared using a 21, 51 full-factorial design where the impact of lecithin concentration and additives were investigated. The optimum ethosomal vesicles were subsequently incorporated in Carbopol gel base where rheological behavior, spreadability, mucoadhesion, and in vivo pharmacokinetic parameters were studied. Based on Design Expert® software (Stat Ease, Inc., Minneapolis, MN), the optimum formulation illustrated entrapment efficiency of 70.02%±5.52%, and vesicular size of 112 ± 3.3 nm, polydispersity index of 0.32 ± 0.01, zeta potential of −59 ± 0.28 mV, and % drug released after 6 h of 76.30%±2.45%. Moreover, ex vivo permeation through rabbit intestinal mucosa increased four times compared to free DOM suspension. The gel loaded with ethosomes showed excellent mucoadhesion to rectal mucosa. DOM ethosomal gel showed a raise in Cmax and AUC0-48 of DOM by twofolds compared to free DOM gel. The study suggested that ethosomes incorporated in gels could be an efficient candidate for rectal transmucosal delivery of DOM.